The Immunogenicity and Anti-tumor Efficacy of a Rationally Designed Neoantigen Vaccine for B16F10 Mouse Melanoma - Zhang, Yan; Lin, Zhibing; Wan, Yuhua; Cai, Huaman; Deng, Li; Li, Rongxiu (Frontiers in Immunology, 2019)
Tumor neoantigens are ideal targets for cancer immunotherapy as they are recognized by host immune system as foreigners and can elicit tumor-specific immune responses. However, existing strategies utilizing RNA or long peptides for the neoantigen vaccines render limited immune responses since only 20%-30% of neoantigens predicted in silico to bind MHC I molecules are capable of eliciting immune responses with the majority of neoantigen-specific T cell responses are CD4+. Therefore, it warrants further investigation to improve CD8+ T cell response rates for neoantigens. Since neoantigens are naturally weak antigens, we asked whether foreign T help epitopes could enhance immunogenicity of such weak antigens. Here, we chose four weak B16F10 neoantigens as vaccine targets, and fused them to the transmembrane domain of diphtheria toxin, namely DTT-neoAg. Strikingly, the vaccine elicited anti-tumor CD8+ T cell responses and enhanced T cell infiltration in tumor. Impressively, DTT-neoAg vaccine significantly deter tumor growth with the inhibition rate reached 88% in the preventive model and 100% in therapeutic model with low dose of tumor challenge. Furthermore, after second challenge with higher dose of tumor cells, 33.3% of the immunized mice remain tumor-free for 6 months in the therapeutic model. Because DTT is a nontoxic domain of diphtheria toxin, it may be not of great concern in terms of safety as a Th epitope provider. Thus the fusion strategy employed by this study may become a feasible and powerful approach for development of personalized cancer vaccine.